Effects of Killari earthquake on the paleo-channel of Tirna River Basin from Central India using anisotropy of magnetic susceptibility - Lakshmi, B. V.; Deenadayalan, K.; Gawali, Praveen B.; Misra, Saumitra (My University, 2020)
The Killari Earthquake (Moment magnitude 6.1) of September 30, 1993, occurred in the state of Maharashtra, India, has an epicenter (18°03′ N, 76°33′ E) located at ~ 40 km SSW of Killari Town. The ~ 125 km long basin of Tirna River, close to the Killari Town, currently occupies the area that has witnessed episodic intra-cratonic earthquakes, including the Killari Earthquake, during last 800 years. The anisotropy of magnetic susceptibility (AMS) study was performed on ~233 soft sedimentary core samples from six successions located in the upper to lower stream of the Tirna River basin in the present study in order to evaluate the efects of earthquake on the river fow dynamics and its future consequence. The AMS Kmax orientations of the samples from the upper reach of the river section suggest that the sedimentation in this part of the river was controlled by a N–S to NNW–SSE fuvial regime with a low or medium fow velocity. In the middle reaches of the basin, an abrupt shift in the palaeo-fow direction occurred to W–E with low velocity fow. However, a NW–SE higher palaeo-fow regime is identifed in the following central part of the basin in down-stream direction, followed by a low-velocity palaeo-fow regime at the lower reach of the Tirna basin. We attribute the sudden high fow velocity regime in the central part of the river basin to an enhanced gradient of the river that resulted from the reactivation of a NW–SE fault transecting the Tirna River basin at the Killari Town. As the NW–SE faulting in regional scale is attributed as the main cause of Killari Earthquake, the reactivation of this fault, thus, could enhance the further possibility of an earthquake in near future, and hence leading to devastating food in the almost fat-lying downstream part of the Tirna River.
Keywords: Killari earthquake; Tirna River Basin; Magnetic susceptibility